Coincidence criteria for the kernel of a function and the kernel of its integral almost positive means - Usenko, E. G. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish necessary and sufficient conditions for a point A of the Knopp kernelK(f) of a functionf to belong to the kernelK(M) of a functionM(t):=∫ S fdμ t , where the so-called almost positive measures μ t determine a regular method of summation. In particular, this gives coincidence criteria for the kernelsK(f) andK(M).